Course Delivery: Keystones of Effective Special Education Teacher Preparation. (February 2014) - Vernon-Dotson, Lisa J.; Floyd, Loury O.; Dukes, Charles; Darling, Sharon M.
In this review of the literature, the authors examined studies investigating course delivery methods for preparing special education teachers. Ultimately, 17 studies were reviewed using a constant comparative qualitative method of analysis. This analysis led to the emergence of five themes: (a) established needs, (b) effectiveness, (c) logistics, (d) instructional methods, and (e) critical factors. The findings from this review are discussed in relation to mechanisms affecting special education teacher education, including (a) technology, (b) diversity, (c) preservice and in-service prerequisite knowledge, (d) skills and dispositions, and (e) program quality. Implications for future research in distance education related to special education teacher preparation, such as need for variability in the courses types are examined, while the necessity for studies utilizing random selection and implications for practice pertaining to instructor and student readiness as well as program infrastructure are suggested.